Poverty in Indonesia and Poverty Alleviation Efforts: A Literature Review - Ramadani, Novi; Batubara, Nur Fadhilla (Al'Adzkiya Journal, 2024)
Poverty is a condition of a person or group of people who are unable to fulfill the basic rights of life in order to survive and be able to develop a dignified life. Poverty can lead to increased unemployment, school dropouts, health problems, and increased crime. Poor people may find it difficult to access proper education. This research aims to find out the opportunities in improving poverty alleviation efforts in Indonesia. The author also discusses the factors that cause poverty in Indonesia, the impact of poverty, private institutions that have an important role in overcoming poverty, opportunities in improving alleviation efforts, the impact of bullying, and social support received by victims. This research is a literature review by searching the literature in several online databases such as Google and Google Scholar. As a result, Indonesia can improve poverty alleviation through the use of technology, inclusive education, and access to the labor market. These efforts require synergy between the government, non-governmental organizations, the private sector, and society at large to achieve optimal results.